1997
DOI: 10.1097/00001756-199711100-00032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bromocriptine on human subjects depend on working memory capacity

Abstract: Pharmacological manipulation of brain dopamine concentration affects visuospatial working memory in humans and in animals, the latter effects localized to the prefrontal cortex. However, the effects of dopamine agonists on humans are poorly understood. We hypothesized that bromocriptine would have an effect on cognitive functions associated with the prefrontal cortex via its effects on cortical dopamine receptors and on subcortical receptors in areas that project to the neocortex. We found that the effect of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
315
5
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 383 publications
(360 citation statements)
references
References 12 publications
35
315
5
5
Order By: Relevance
“…This characteristic inverted U-shape function is thought to explain DA actions on cognition as a function of individuals' overall baseline performance. Animals (Granon et al, 2000) and humans (Kimberg et al, 1997;Mattay et al, 2000;Mehta et al, 2000) performing low at baseline profited from the substance and those performing high at baseline deteriorated after substance intake. Thus, applied to the present study, individuals performing low in the substance-free state (high MI scorers in Experiment 1 and the placebo group of Experiment (2) performed best in the levodopa group.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic inverted U-shape function is thought to explain DA actions on cognition as a function of individuals' overall baseline performance. Animals (Granon et al, 2000) and humans (Kimberg et al, 1997;Mattay et al, 2000;Mehta et al, 2000) performing low at baseline profited from the substance and those performing high at baseline deteriorated after substance intake. Thus, applied to the present study, individuals performing low in the substance-free state (high MI scorers in Experiment 1 and the placebo group of Experiment (2) performed best in the levodopa group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, structural equation modelling suggests that the tasks often used in cognitive and neuropsychological studies to explore executive functioning are not completely homogeneous in the sense that the three executive functions isolated contribute differentially to performance on complex executive tasks. For example, performance on the Wisconsin Card Sorting Test (computerised version developed by Kimberg, D'Esposito & Farah, [67] was related most strongly to the shifting function while performance on the Tower of Hanoi [58] depends on inhibition processes. The only complex executive task that did not relate clearly to the three target executive functions was the dual task (requiring the simultaneous performance of a spatial maze task and a verbal word generation task).…”
Section: The Central Executive Of Working Memorymentioning
confidence: 99%
“…In the interpretation of psychopharmacological studies of cognition, the influence of baseline performance on subsequent response to a drug challenge has been discussed by a number of authors (Robbins and Sahakian 1979;Kimberg et al 1997;Mattay et al 2000;Mehta et al 2000). Tasks of working memory and executive function may be both impaired (Kimberg et al 1997) or improved (Kimberg et al 1997;Mehta et al 2000) following dopaminergic agonists, dependent on baseline working memory capacity.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Tasks of working memory and executive function may be both impaired (Kimberg et al 1997) or improved (Kimberg et al 1997;Mehta et al 2000) following dopaminergic agonists, dependent on baseline working memory capacity. Using the stimulant, amphetamine, Mattay et al (2000) demonstrated that such baseline-dependent cognitive effects may be paralleled by changes in brain activity as indexed by functional magnetic resonance imaging BOLD signal.…”
Section: Letter To the Editormentioning
confidence: 99%